PENGARUH RESTRIKSI KALORI TERHADAP KADAR HIDROGEN PEROKSIDA DAN KADAR GLUKOSA DARAH PADA TIKUS TUA - E. Harianja; Anik Widijanti; Putu Moda Arsana; K. Handono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Aging is a syndrome of progressive, universal and irreversible alterations. Endocrinology alterations in aging consist of insulin resistance, hyperinsulinemia, increase of hydrogen peroxide and glucose blood level. At the beginning of aging process the Pancreaticcellsproducemoreinsulininorderiskeepbloodglucosewithinnormallevel.Butthepersistentofhyperglycemiaconditioncausedthepancreatic-cellsunabletoproduceadequateinsulinduetointernalfactorsorexternalfactors.Asthisconditionprogress,wouldbedisturbedfastingandpost-prandialbloodglucose(hyperglicemia).Besidesinsulinresistance,freeradicalsalsoincreasedasaconsequenceoffailurecompensationofcellsinthebody.TheaimofthisstudyistodeterminethatintermittentanddailycalorierestrictioninoldmaleWistarratscanreduceserumhydrogenperoxide,andbloodglucoselevel.Themethodofthisstudywasanexperimentalstudywithpost-testcontrolgroupdesign.TwentyfourmaleWistarratsabout12monthsold,weredividedintofourequalgroupsandeachgroupcontainsixrats:(i)adlibitumfed(control),(ii)2-1intermittentwith2daysfedand1dayfast,(iii)1-1intermittentwith1dayfedand1dayfast,and(iv)40%continuouscalorierestrictioneveryday.Independentvariableinthisstudywascalorieintakeandbodyweight.Dependentvariableswerehydrogenperoxideleveland.Bloodglucoselevel.Thedifferenceofeachgroupwasanalyzedwithone way ANOVA and the least significant difference was analyzed by the use post hoc tests, using p < 0.05. The result of this study for hydrogen peroxide and blood glucose level in control group with experimental groups were p 0.000 and p 0.001. There was positivecorrelation between hydrogen peroxide level and blood glucose level r 0.791. We conclude that calorie restriction decrease hydrogenperoxide level and as well as regulating of blood glucose level. The best one of this method is 40% calorie restriction.